Analysis of meaning of Keisya Levronka's song Tak Ingin Usai - Sauma Nadia Azzahro; Sri Utami (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Abstract : This research focuses on the lexical and grammatical meanings in the lyrics of Keisya Levronka's song "Tak Lagi Usai". This study uses a semantic approach. The purpose of this study is to first explain the grammatical meaning in the lyrics of the song "Tak Lagi Usai" by Keisya Levronka. The second explains the lexical meaning in the lyrics of Keisya Levronka's song "Unwanted to End". The research method used is descriptive qualitative method. This research is descriptive qualitative which means using interpretation (interpretative). The source of the data used is the song "Unwanted to End" by Keisya Levronka. The data analysis technique used is note-taking, namely by analyzing the grammatical and lexical meanings contained in the lyrics of the song "Tak Lagi Usai" by Keisya Levronka. The data in this study are all words, phrases, clauses, and sentences contained in the lyrics of Keisya Levronka's song "Tak Lagi Usai" which contain grammatical and lexical meanings. The results of the research conducted by the researcher concluded that there were 40 data, namely the first data of grammatical meaning, there were 22 data. Then the second data about lexical meaning there are 18 data.